Understanding the awareness of publication ethics among medical postgraduate trainees in India: A web-based survey - Keerthi Talari; Mohit Goyal (Indian Journal of Rheumatology)
Background: Postgraduate training is often the first stage where a medical trainee is required to research and publish. With no or scant prior training and the pressure to publish, it is potentially a stage where ethical lapses and publishing misconducts are likely to occur. We conducted a web-based survey among medical postgraduate trainees in India to assess their awareness about publication ethics and identify the specific areas where they lacked awareness. Methods: This was a cross-sectional, web-based survey conducted among medical postgraduate trainees in India. A Google form with multiple choice type questionnaire comprising 10 items related to publication ethics was prepared and disseminated after checking its face and content validity. The questionnaire included items to assess awareness about informed consent, plagiarism, authorship issues, conflict of interest, data handling, and predatory publications. Results: A total of 205 responses were analyzed. While the respondents had better awareness about the informed consent, sample size and consequences of data fabrication (correct responses by 55%, 66%, and 77% of respondents, respectively), the responses to other questions (direct plagiarism, duplicate submission, authorship issues, reviewer's conflict of interest, conflict of interest, salami publication, and predatory journals) were varied and demonstrated a greater degree of ignorance. Majority of the respondents were unaware that a manuscript cannot be submitted to multiple journals at the same time. Conclusion: This survey shows that postgraduate medical trainees lacked adequate awareness of publication ethics. Structured approaches involving curricular exposure, focused workshops, and special courses covering these aspects may result in better awareness regarding these issues.